Hsa_circ_0060450 Negatively Regulates Type I Interferon-Induced Inflammation by Serving as miR-199a-5p Sponge in Type 1 Diabetes Mellitus - Yang, Lan; Han, Xiao; Zhang, Caiyan; Sun, Chengjun; Huang, Saihua; Xiao, Wenfeng; Gao, Yajing; Liang, Qiuyan; Luo, Feihong; Lu, Wei; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2020)
Circular RNAs (circRNAs) constitute a class of covalently circular non-coding RNA molecules formed by 5′ and 3′ end back-splicing. The rapid development of bioinformatics and large-scale sequencing has led to the identification of functional circRNAs. Despite an overall upward trend, studies focusing on the roles of circRNAs in immune diseases remain relatively scarce. In the present study, we obtained a differential circRNA expression profile based on microarray analysis of peripheral blood mononuclear cells (PBMCs) in children with type 1 diabetes mellitus (T1DM). We characterized one differentially expressed circRNA back-spliced from the MYB Proto-Oncogene Like 2 (MYBL2) gene in patients with T1DM, termed as hsa_circ_0060450. Subsequent assays revealed that hsa_circ_0060450 can serve as the sponge of miR-199a-5p, release its target gene, Src homology 2 (SH2)-containing protein tyrosine phosphatase 2 (SHP2), encoded by the tyrosine-protein phosphatase non-receptor type 11 gene (PTPN11), and further suppress the JAK-STAT signaling pathway triggered by type I interferon (IFN-I) to inhibit macrophage-mediated inflammation, which indicates the important roles of circRNAs in T1DM and represents a promising therapeutic molecule in the treatment of T1DM.